THE INFLUENCE OF BODY MASS INDEX ON THE MENSTRUAL CYCLE IN ADOLESCENTS: Pengaruh Indeks Massa Tubuh terhadap Siklus Menstruasi pada Remaja - Dwi Artanti, Kurnia; Sutera Dewangga, Angelinasyarga; Azrielda Munib, Tazkia; Hidayat, Taufiq (Universitas Airlangga, 2025)
Background: Imbalanced nutritional status in adolescents can affect the menstrual cycle. In 2018, the WHO stated that as many as 80% of women in the world have irregular menstrual cycles. More specifically, this condition is experienced by 11.70% of adolescents aged 15-19 years and 14.90% of women in urban areas. Purpose: To analyze the effect of body mass index (BMI) on the menstrual cycle in adolescents at Junior High School State 19 Surabaya. Methods: This quantitative research employed an observational analytic method with a case-control design at SMP Negeri 19 Surabaya. As many as 104 participants (52 cases with irregular menstrual cycles and 52 controls with regular cycles) were randomly selected in a 1:1 ratio. Data collection occurred from February to May 2024, and bivariate analysis was conducted using the Chi-square test. Results: This study showed that overall BMI had a significant effect on menstrual cycle regularity (p = 0.001). Students with normal BMI have a greater chance of experiencing regular menstruation than overweight/obese (OR = 4.694; 95% CI = 1.536 - 14.344; p = 0.007). Meanwhile, the categories of very thin (OR = 0.985; 95% CI = 0.235 - 4.127; p = 0.983) and underweight (OR = 0.433; 95% CI = 0.072 - 2.622; p = 0.363) did not show a significant influence on menstrual regularity (p > 0.05). Conclusion: Body mass index affects menstrual cycle regularity in adolescents. Maintaining nutritional status is important to minimize the risk of menstrual cycle disorders and ensure reproductive health.